The Bajanama Inscription of Jagatasena - Das, Basudevlal (Academic Voices: A Multidisciplinary Journal, 2013)
The Sena dynasty was established in Nepal after its downfall in Bengal. The Senas were orthodox Hindus. The kingdom of Makawanpur was ruled by the kings of Sena dynasty. Janakpur was situated within its territory. The condition of Janaki Temple Monastery of Janakpur became pitiable and the monk called the king for the betterment of the monastery. But the state was unable to do, so the Bajanama, a kind of desistance paper, was given in 1733 AD. This paper is written to thirough lights on the matters of economic condition of the state, the official language which is a mixed form of Hindi, Bhojpuri and Urdu words and the writing of script Nagari. Academic Voices, Vol. 2, No. 1, 2012, Pages 1-4 DOI: http://dx.doi.org/10.3126/av.v2i1.8276